Why Jews can also be called Israelites. A new approach to the question of “Biblical Israel” - Schütte, Wolfgang (Antiguo Oriente, 2021)
Why Jews can also be called Israelites. A New Approach to the Question of “Biblical Israel” The gentilicium Jew as well as the historically differentiating terms Judahite and Judaean refer back histo rically to inhabitants of the Judah region. An analysis of biblical texts reveals three stages in which the name Israel first pene trated Judaean society through Israelites, reshaped the Judahite community and finally shaped the image of Jews who saw themselves exclusively as Israelites.